Analysis of water quality of godavari river at Ahmednagar District, Maharashtra - Tejaswini Kande; Supriya Khatal; Pallavi Dhekale; Vikas Thorat; Priyanka Borude; Ashok Bhosale (International Journal of Pharmacy and Analytical Research, 2022)
Water pollution is one of the major global environmental problems. It is an acute problem almost in all major rivers and water reservoirs in India. Water pollution is increasing and becoming severe day-by-day and posing a great risk to human health and other living organisms. There is growing concern on the deterioration of ground water quality due to geogenic and anthropogenic activities. Present investigation aims at insight about the level of contaminants of surface water, groundwater and sediment analysis of selected rivers of Godavari River located in Puntamba, Gaon, Taluka shrirampur, Ahmednagar district. An attempt has been made to assess the water quality, Godavari River DO was 12.4 mg/L. In the present study, COD value was observed by 169 mg/l at surface water of Godavari River. As expected groundwater samples showed values of hardness within a limit. There is an urgent need for more representative samples to be used to go beyond preliminary assessment as reported in the present study for making appropriate recommendations.